Autosomal recessive truncating MAB21L1 mutation associated with a syndromic scrotal agenesis. Issue 2 (5th June 2016) - Bruel, A.‐L.; Masurel‐Paulet, A.; Rivière, J.‐B.; Duffourd, Y.; Lehalle, D.; Bensignor, C.; Huet, F.; Borgnon, J.; Roucher, F.; Kuentz, P.; Deleuze, J.‐F.; Thauvin‐Robinet, C.; et al.
Abstract : Description of a boy from consanguineous family, with scrotal agenesis and Dandy‐Walker malformation. Abstract : We report on a boy with a rare malformative association of scrotum agenesis, ophthalmological anomalies, cerebellar malformation, facial dysmorphism and global development delay. The reported patient was carrying a homozygous frameshift in MAB21L1 detected by whole‐exome sequencing, considered as the most likely disease‐causing variant. Mab21l1 knockout mice present a strikingly similar malformative association of ophthalmological malformations of the anterior chamber and preputial glands hypoplasia. We hypothesize that MAB21L1 haploinsufficiency cause a previously undescribed syndrome with scrotal agenesis, ophthalmological anomalies, facial dysmorphism and gross psychomotor delay as remarkable hallmarks. Four cases from the literature were reported with features suggestive of a similar and recognizable clinical entity. We hypothesize that MAB21L1 should be the culprit gene in these patients.